2019
DOI: 10.3390/molecules24152813
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Bioindication Potential of the Common Weeds Senecio vulgaris L., Polygonum aviculare L. and Poa annua L.

Abstract: In recent years, heavy metals (HMs) levels in soil and vegetation have increased considerably due to traffic pollution. These pollutants can be taken up from the soil through the root system. The ability of plants to accumulate HMs into their tissues can therefore be used to monitor soil pollution. The aim of this study was to test the ruderal species Senecio vulgaris L., Polygonum aviculare L., and Poa annua L., as possible candidates for biomonitoring Cu, Zn, Cd, Cr, Ni and Pb in multiple environments. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 52 publications
(63 reference statements)
1
22
0
Order By: Relevance
“…Our results pointed out that the amounts of the six tested metals, detected in the shoots of both species, were directly proportional to their concentration in the hydroponic culture media ( Figure 1 and Figure 2 ). As a consequence of this proportional absorption, the studied species could be considered good indicator plants, confirming previous results that proved S. vulgaris to be a viable Ni indicator in different soil environments [ 29 ]. According to the present data, P. aviculare was more efficient than S. vulgaris in preventing metal absorption, going towards an excluder behavior, especially in the presence of Cd and Pb.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Our results pointed out that the amounts of the six tested metals, detected in the shoots of both species, were directly proportional to their concentration in the hydroponic culture media ( Figure 1 and Figure 2 ). As a consequence of this proportional absorption, the studied species could be considered good indicator plants, confirming previous results that proved S. vulgaris to be a viable Ni indicator in different soil environments [ 29 ]. According to the present data, P. aviculare was more efficient than S. vulgaris in preventing metal absorption, going towards an excluder behavior, especially in the presence of Cd and Pb.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results are usually unachievable when these plants are cultivated in the soil, where metals are less bioavailable. In fact, data on P. aviculare and S. vulgaris collected from natural soils showed that these species were not capable of concentrating HMs in the shoots, having in most cases BAFs below 0.3 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations